Hand trauma illustrated surgical guide of core procedures - Nikkhah, Dariush (Thieme, 2018)
Surgical treatment of hand trauma is a highly complex form of surgery that requires mastery of several different disciplines, including microsurgery of blood vessels less than 1 mm in diameter, osteosynthesis, and flap coverage of traumatic defects. This work intends to provide clear, practical guidance to the less experienced so that they gain confidence in carrying out the core procedures involved in the surgical management of hand trauma.